Avaliação do estado nutricional e do hábito alimentar de pacientes oncológicos no município de Coari, Amazonas - Vieira, Adriana (Brasil, 2024)
Introduction: Cancer is a chronic disease characterized by the uncontrolled growth of cells that invades adjacent tissues and organs, spreading to other regions of the body. Objective: Assessing the dietary habits and nutritional status of three oncology patients in the municipality of Coari, Amazonas. Method: This is a longitudinal study conducted on three cancer patients in the municipality of Coari-AM during July and August 2023, with data collection continuing into 2024 as part of a larger longitudinal project. A questionnaire was administered to gather sociodemographic information, and another questionnaire was used to collect clinical data. Dietary intake was assessed using the Food Frequency Questionnaire and 24-hour Dietary Recall. Data analysis involved descriptive analysis, presenting measures of central tendency such as mean and standard deviation. Results: The study investigated the dietary habits and nutritional status of three cancer patients (average age: 70.6 years) – two women with uterine and breast cancer, and one man with head cancer. They were respectively diagnosed with mild malnutrition, overweight, and obesity. Notably, only one of them exhibited symptoms of loss of appetite. Conclusion: Nutritional diagnoses reveal a complex reality, encompassing not only the presence of malnutrition but also cases of overweight and inadequate nutrient intake.